Protestant Portrayals of Islam: From the Reformation to Modern Missions - Womack, Deanna Ferree (Interpretation, 2022)
This study compares Protestant portrayals of Islam during the sixteenth-century Protestant Reformation and the nineteenth-century era of imperialism and missions. It considers the earliest Protestant writings about Islam and the views of the first Protestant missionaries who had close personal contact with Muslims. To understand the historical thought patterns that still influence contemporary American Protestant views of Muslims, the article examines common theological themes, statements about women and sexuality, rhetoric about Islamic violence, and shifting approaches to Muslims over the centuries. While addressing misrepresentations of Islam, this study finds that Protestant understandings of Islam are not always skewed or hostile. Religious rivalry and condemnation have made a lasting impact, yet this history also reveals appreciative views of Islam from which we could learn today.